2015
DOI: 10.1371/journal.pone.0120400
|View full text |Cite|
|
Sign up to set email alerts
|

Multigene Assessment of the Species Boundaries and Sexual Status of the Basidiomycetous Yeasts Cryptococcus flavescens and C. terrestris (Tremellales)

Abstract: Cryptococcus flavescens and C. terrestris are phenotypically indistinguishable sister species that belong to the order Tremellales (Tremellomycetes, Basidiomycota) and which may be mistaken for C. laurentii based on phenotype. Phylogenetic separation between C. flavescens and C. terrestris was based on rDNA sequence analyses, but very little is known on their intraspecific genetic variability or propensity for sexual reproduction. We studied 59 strains from different substrates and geographic locations, and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 69 publications
4
31
0
Order By: Relevance
“…3). These four strains remain unidentified, because a high degree of genetic heterogeneity within P. flavescens has been reported (Yurkov et al 2015), and thus further analysis is needed for identification.…”
Section: Yeast Isolation and Identificationmentioning
confidence: 99%
“…3). These four strains remain unidentified, because a high degree of genetic heterogeneity within P. flavescens has been reported (Yurkov et al 2015), and thus further analysis is needed for identification.…”
Section: Yeast Isolation and Identificationmentioning
confidence: 99%
“…Studies with a similar scope on other tetrapolar species (viz. K. mangrovensis, K. heveanensis, Cryptococcus flavescens, and C. terrestris (Tremellales, Agaricomycotina) (Metin et al 2010;Guerreiro et al 2013;Yurkov et al 2015) readily detected arbitrary assortment of MAT alleles, even within a more restricted number of isolates. Although we cannot rule out that other mechanisms may cause the apparent nonrandom association between P/R (A) and HD (B) loci in L. scottii, we highlight two possibilities in particular.…”
Section: Mat Allele Diversity In the L Scottii Species Complexmentioning
confidence: 99%
“…Liu et al (2015a) recognized the aureus clade as monophyletic, although they included only Cryptococcus aureus, Cryptococcus flavescens and Cryptococcus terrestris in their analysis, and suggested that new genera need to be proposed to accommodate the monophyletic clades within tremellomycetous yeasts. Two additional cryptic species in the aureus clade, C. baii and C. ruineniae, were described based on multigene analysis (Yurkov et al, 2015). In order to avoid new genera for aureus, Auriculibuller, laurentii, Papiliotrema and pseudoalba clades, Liu et al (2015b) accommodated these small clades in the genus Papiliotrema.…”
Section: Strains Cbs 8358mentioning
confidence: 99%
“…Kurtzman (1973), however, reported sexual activity with strains of Cryptococcus laurentii. In addition, Yurkov et al (2015) detected genetic recombination and the presence of sexual reproduction related genes (MAT genes) in P. flavescens and P. terrestris, although they failed to induce mating. The authors suggest that their failure could be due to the need of specific media components or conditions for sexual reproduction, and not to an intrinsic inability of the strains to mate.…”
Section: Strains Cbs 8358mentioning
confidence: 99%
See 1 more Smart Citation